Epigentic technological applications - George Zheng [editor] (Translational epigenetics series., 2015)
Epigenetic Technological Applications is a compilation of state-of-the-art technologies involved in epigenetic research. Epigenetics is an exciting new field of biology research, and many technologies are invented and developed specifically for epigenetics study. With chapters covering the latest developments in crystallography, computational modeling, the uses of histones, and more, Epigenetic Technological Applications addresses the question of how these new ideas, procedures, and innovations can be applied to current epigenetics research, and how they can keep pushing discovery forward and beyond the epigenetic realm.